2016
DOI: 10.1124/jpet.115.231696
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Natriuretic Peptide Improves Left Ventricular Functional Performance at Rest and Restores Normal Exercise Responses after Heart Failure

Abstract: In heart failure (HF), the impaired left ventricular (LV) arterial coupling and diastolic dysfunction present at rest are exacerbated during exercise. C-type natriuretic peptide (CNP) is elevated in HF; however, its functional effects are unclear. We tested the hypotheses that CNP with vasodilating, natriuretic, and positive inotropic and lusitropic actions may prevent this abnormal exercise response after HF. We determined the effects of CNP (2 mg/kg plus 0.4 mg/kg per minute, i.v., 20 minutes) on plasma leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In a mouse model of cardiac hypertrophy and remodelling induced by angiotensin II, CNP infusion also increased fractional shortening and decreased LVED dimension compared to the angiotensin II vehicle group, but no changes were observed with CNP when comparing with vehicle in the saline groups (Izumiya et al., 2012 ). In pacing‐induced HF in dogs, CNP augmented LV contraction, relaxation, diastolic filling and LV arterial coupling (Li et al., 2016 ). Taken collectively, observations in vivo suggest that CNP elicits both inotropic and lusitropic responses in preclinical models of HF.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of cardiac hypertrophy and remodelling induced by angiotensin II, CNP infusion also increased fractional shortening and decreased LVED dimension compared to the angiotensin II vehicle group, but no changes were observed with CNP when comparing with vehicle in the saline groups (Izumiya et al., 2012 ). In pacing‐induced HF in dogs, CNP augmented LV contraction, relaxation, diastolic filling and LV arterial coupling (Li et al., 2016 ). Taken collectively, observations in vivo suggest that CNP elicits both inotropic and lusitropic responses in preclinical models of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CNP treatment reduces fibroblast collagen production and stimulates osteoblast and endothelial cell differentiation 37 38 . In vivo , CNP has been shown to be cardioprotective by improving left ventricle capacities after heart failure in dogs, by preventing cardiomyocyte hypertrophy in infarcted mouse hearts and by increasing cardiomyocyte relaxation and inotropic response in failing rat hearts 34 39 40 41 . Here in this report we showed that CNP is able to stimulate the proliferation of the cardiac Sca-1 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Rats in groups P1 and P2, C1, and C2 then received a normal saline infusion and the rats in group P3 and C3 were treated with CNP (CNP-53, The Peptide Institute, Osaka, Japan). CNP was given with a 2 μ g/kg loading dose plus a 0.4 μ g/kg/min infusion for 20 minutes [9]. Data were then recorded after 1 hour at T2.…”
Section: Methodsmentioning
confidence: 99%